Pengaruh Kemampuan Komunikasi Sosial Dan Kemandirian Belajar Terhadap Hasil Belajar Mata Pelajaran Ilmu Pengetahuan Sosial (IPS) Siswa Kelas VIII Di Surabaya - Niken Rahayu (Jurnal Dialektika Pendidikan IPS, 2026)
This study investigates the influence of social communication skills and learning independence on the social studies learning outcomes of eighth-grade students in junior high schools in Surabaya using a quantitative associative approach with purposive sampling with 146 students from 3 elementary school. Data were collected through questionnaires and learning-outcome documentation, then analyzed using multiple linear regression. The findings indicate that both social communication skills and learning independence positively and significantly affect social studies learning outcomes, either individually or simultaneously, with a correlation coefficient of 0.840 indicating a very strong relationship, and social communication skills emerging as the most dominant predictor. These results highlight the importance of strengthening students’ communication and independent learning abilities, while encouraging teachers and schools to create interactive learning environments, and suggesting future studies to expand the sample and include additional variables such as learning motivation or parental support. Keyword: Behavior, Facilities, Waste, River